Energy potential and environmental benefits of agricultural crop biomass resources in Henan Province, China - Liu, Tingting; Tian, Liying; Wen, Ping; Sun, Tianhua; Zhao, Cuiping (International Journal of Agricultural and Biological Engineering, 2026)
Henan Province, as one of China’s largest grain production bases, produces abundant agricultural crop biomass resources every year, yet the environmental benefits from their applications remain underutilized. This study systematically investigates the theoretical and collectable outputs of major agricultural crop biomass resources in Henan from 2013 to 2023. The results show that Henan Province annually produces, on average, 1.09×108 t of theoretical and 8.73×107 t of collectable agricultural crop biomass resources, with an energy potential of about 4.44×107 t of standard coal equivalent (tce), accounting for about 19.7% of Henan’s average annual energy consumption. Among these resources, maize stalk and wheat straw predominate, together contributing nearly four-fifths of the total agricultural crop biomass energy potential in Henan. Scenario analyses indicate that utilizing 1.485×107 t of agricultural crop biomass resources for energy could reduce 1.574×107 t of CO2 emissions through combustion and up to 3.36×107 t of CO2 emissions through pyrolysis with biochar application to soil. These findings indicate the significant role of agricultural crop biomass in supporting Henan’s transition to sustainable energy and its carbon mitigation efforts. Keywords: agricultural crop biomass, energy potential, environmental benefits, energy conversion, pyrolysis with biochar application DOI: 10.25165/j.ijabe.20261901.10160 Citation: Liu T T, Tian L Y, Wen P, Sun T H, Zhao C P. Energy potential and environmental benefits of agricultural crop biomass resources in Henan Province, China. Int J Agric & Biol Eng, 2026; 19(1): 153–162.